1989
DOI: 10.1111/j.1464-410x.1989.tb05976.x
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Monitoring of Bladder Pressures in Patients with Low Compliance as a Result of Neurogenic Bladder Dysfunction

Abstract: A group of 28 patients with neurogenic bladder dysfunction and low bladder compliance was studied using medium fill cystometry (CMG) and ambulatory monitoring (AM) during natural bladder filling. The aims of the study were to compare the 2 techniques and to determine if ambulatory monitoring might be useful in predicting upper tract dilatation. AM demonstrated significantly lower end filling pressures compared with CMG. Phasic detrusor contractions were found more commonly during AM and the frequency of phasic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…On the other hand, maximum voiding pressure and bladder compliance were higher than the conventional baseline data. Our results are similar to those recorded in most previous studies on ambulatory monitoring [Griffiths et al, 1987Webb et al, 1989Webb et al, , 1990Webb et al, , 1991Styles et al, 19881. Resting pressures recorded by the telemetry monitoring system were consistently higher than the resting pressures recorded during the conventional method. The explanation of this difference may be due to the pressures recorded during telemetry that are referred to the tips of the transducers at the site of their implantation whereas the pressures measured by the conventional method are referred to the transducers at the height of the symphysis pubis [Abrams et al, 19881.…”
Section: Discussionsupporting
confidence: 95%
“…On the other hand, maximum voiding pressure and bladder compliance were higher than the conventional baseline data. Our results are similar to those recorded in most previous studies on ambulatory monitoring [Griffiths et al, 1987Webb et al, 1989Webb et al, , 1990Webb et al, , 1991Styles et al, 19881. Resting pressures recorded by the telemetry monitoring system were consistently higher than the resting pressures recorded during the conventional method. The explanation of this difference may be due to the pressures recorded during telemetry that are referred to the tips of the transducers at the site of their implantation whereas the pressures measured by the conventional method are referred to the transducers at the height of the symphysis pubis [Abrams et al, 19881.…”
Section: Discussionsupporting
confidence: 95%
“…Webb et al (8,9) studied 66 patients with bladder dysfunction due to diverse neurological aetiologies (53 males and 13 females). The patients were selected because of high bladder pressures (!25 cmH 2 O) during rapid artificial bladder filling (100 ml/min) and 22 had dilated upper urinary tracts at the time of study.…”
Section: Neurogenic Bladder Dysfunctionmentioning
confidence: 99%
“…Comparison of detrusor pressure rise during natural bladder filling (AM), slow and medium fill cystometry in six patients with low compliance due to neurogenic bladder dysfunction9 …”
mentioning
confidence: 99%
“…Similarly, Webb et al [68] showed that AUM could identify those neurogenic bladder populations at high risk for upper tract deterioration by detecting greater resting pressures and increased detrusor activity during natural filling. In contrast, conventional cystometrography (CMG) was not as accurate in identifying those patients who had developed renal changes [68].…”
Section: Clinical Usefulness Of Ambulatory Urodynamic Monitoringmentioning
confidence: 97%